Las grandes empresas del Ecuador controladas por la Superintendencia de Compañías, su inversión en activos y resultados globales - Malla Alvarado, Franklin Yovani (2018)
This analysis refers to the main companies that, due to their legal status, are under the supervision and control of the Superintendence of Companies of Ecuador, the data have been taken from the regulatory portal and are the basis for determining that the organizations not always invest more in assets and therefore those have necessarily greater profitability. Rather their internal strategies and policies allow them to reach the levels of surplus expected by their investors over time. In addition, an approach is made to the regional environment of Planning Zone 7, made up of the provinces of Loja, El Oro and Zamora Chinchipe, in order to find out in which medium the companies that are closest to the city of Loja have greater growth and their effect on the different social and economic factors that lead to their growth.